Bordering intimacy : Postcolonial governance and the policing of family (2020)
This book began on an EasyJet flight. Or to be more specific, it began when my partner and I were stopped from getting on an EasyJet flight. In the early hours of the morning we had arrived at the airport to board a flight to Sicily for fieldwork and to attend a conference. As we queued to board the plane with our young son, the airline staff made a further inspection of my partner’s visa documents and her recently acquired family migration visa and marriage certificate. Unsure of the rules that applied to non-EU citizens travelling with family members to the Schengen Area, the airline staff had to contact immigration advisers for their approval for us to fly. Since 2000, as so many of us have become accustomed to, airline carriers bear the responsibility for checking the documentation of anyone boarding a plane. And in doing so they enact the (inter)national border. Whilst the plane waited on the tarmac, it became increasingly clear that the airline staff were not going to risk allowing us to board before they had received an official response from their head office. Whilst having a legal right to travel with myself as an EU citizen to an EU country, my partner needed to confirm this right with the UK Permanent Resident card, which she had yet to acquire. ‘You’ll probably just be deported as soon as you land in Catania’, was the response of the ground staff as they finally confirmed that the plane would leave without us.